Role of 9p21 and 2q36 variants and arterial stiffness in the prediction of coronary artery disease. (August 2014) - Vakalis, Konstantinos; Bechlioulis, Aris; Naka, Katerina K.; Chatzikyriakidou, Anthoula; Gartzonika, Konstantina; Vezyraki, Patra; Kolios, Georgios; Pappas, Konstantinos; Katsouras, Christos S.; Georgiou, Ioannis; Michalis, Lampros K.
Abstract Background Genetic polymorphisms and arterial stiffness indices have been associated with cardiovascular prognosis and the presence and extent of angiographic coronary artery disease (CAD). We aimed to investigate whether arterial stiffness indices and 9p21 and 2q36 variants may improve prediction of CAD presence and extent when added to classical cardiovascular risk factors in patients at high risk for CAD. Materials and methods In this cross‐sectional study, we enrolled 183 consecutive patients with suspected stable CAD (age 61 ± 9 years, 134 males) referred for diagnostic coronary angiography. Framingham risk score (FRS) was calculated. Arterial stiffness was assessed by carotid–femoral pulse wave velocity (PWV) and central augmentation index (AIx) using applanation tonometry. Genetic polymorphisms of 9p21 (rs1333049) and 2q36 (rs2943634) loci were also analysed. Results Higher FRS and PWV and the presence of rs2943634 risk allele were independent predictors of CAD (Nagelkerke R2 0·252, P < 0·001), while higher FRS and the presence of rs1333049 risk allele were independent predictors of multivessel CAD (Nagelkerke R2 0·190, P < 0·001). Genetic polymorphisms and vascular indices did not improve the predictive accuracy of FRS‐based models (P > 0·1 for all) for CAD presence or extent. Conclusions In these high‐risk patients, 9p21 and 2q36 variants and PWV were independently associated with CAD presence and extent, but the addition of both genetic data and arterial stiffness indices to FRS did not improve the prediction of CAD compared with FRS alone. Further studies are needed to clarify the prognostic role of genetic and vascular indices in the prediction of angiographic CAD.